Estudos visando a síntese do (11E,14Z)-hexadeca-11,14-dienal, um possível feromônio sexual de Condylorrhiza Vestigialis (Lepidoptera: Crambidae) - Luis Antonio Giordano Arana Olivari (2019)
In this work, a novel synthetic route for the synthesis of the (11E,14Z)-hexadeca-11,14-dienal, potential sexual pheromone from the Condylorrhiza Vestigialis (Lepidoptera: Crambidae) or the Brazilian poplar moth was proposed starting from two low cost and commercially available reagents: 1,10-decanediol and 2-butyn-1-ol. 7 of the 9 precursors of the desired compound were obtained, isolated andcharacterized by the performance and/or optimization of 12 different reactions. Reactions involved in this work, among others, were diol mono-bromination with HBr reaction, p-TSA catalyzed THP protection and de-protection reactions, acetylide anion alkylation with organolithium precursor. Trimethylsilyl alkyne deprotection, mesylation reactions, (Z)stereoselective catalytic hydrogenation reaction, (E) stereoselective hydrogenation reaction, PBr3 bromination reaction and 1,4- non conjugated unsaturated system formation using acetylide anion alkylation with organocuprate intermediates formed by Gilman reaction andGrignard transmetalation reaction. This work also includes two novel compounds: the (Z)-2-(hexadec-14-en-11-yn-1-yloxy)tetrahydro-2H-pyran, considered as the seventh of the nine precursor for the (11E,14Z)-hexadeca-11,14-dienal compound obtainment, as well as the (E)-2-(hexadec-14-en-11-yn-1-yloxy)tetrahydro-2H-pyran, compound that can be consider of potential interest as a precursor for pheromones synthesis presenting 1,4- non conjugated diene systems.